Farm to school of Park County : a journey from program to nonprofit (A) - Cates, Karen L.; Howard, Liz Livingston (London : Kellogg School of Management, 2019)
The first in a four part case series, this case describes the community, the need, and the origins of Farm to School in Livingston, Montana. The leaders of Farm to School face a budget crisis and need to evaluate four options to decide whether, when, and how it should become an independent organization.
Originally Published InCates, K. L., & Howard, L. L. (2019). Farm to School of Park County: A Journey from Program to Nonprofit (A). 5-418-751(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Small business -- Finance -- Case studies; School children -- Food -- Case studies